2020
DOI: 10.31234/osf.io/zyrvg
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Handedness in ADHD: Meta-Analyses

Abstract: Meta-analyses have shown that several neurodevelopmental and psychiatric disorders, such as autism spectrum disorder and schizophrenia, are associated with a higher prevalence of left- and/or mixed-handedness. One neurodevelopmental disorder for which this association is unclear is attention deficit hyperactivity disorder (ADHD). Here, some empirical studies have found evidence for a higher prevalence of left- and/or mixed-handedness in individuals with ADHD compared to neurotypical individuals. However, other… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 73 publications
(78 reference statements)
0
1
0
Order By: Relevance
“…This is specifically problematic as mixedhandedness has repeatedly been associated with neurodevelopmental and mental disorders. More precisely, meta-analyses confirmed increased rates of mixedhandedness in autism spectrum disorder (Markou et al, 2017), attentiondeficit/hyperactivity disorder (Nastou et al, 2022), dyslexia (Packheiser et al, 2023), posttraumatic stress disorder (Borawski et al, 2022;Goetz et al, 2016) and schizophrenia (Mallet et al, 2022;Sommer et al, 2001). For example, one large cohort study found an increased prevalence of 34.1% for mixed-handedness in subjects diagnosed with schizophrenia (best estimate of the prevalence of mixed-handedness in the general population based on meta-analysis: 9.33%, Papadatou-Pastou et al (2020)) that was further associated with increased positive symptoms and a current depressive episode (Mallet et al, 2022).…”
Section: Introductionmentioning
confidence: 87%
“…This is specifically problematic as mixedhandedness has repeatedly been associated with neurodevelopmental and mental disorders. More precisely, meta-analyses confirmed increased rates of mixedhandedness in autism spectrum disorder (Markou et al, 2017), attentiondeficit/hyperactivity disorder (Nastou et al, 2022), dyslexia (Packheiser et al, 2023), posttraumatic stress disorder (Borawski et al, 2022;Goetz et al, 2016) and schizophrenia (Mallet et al, 2022;Sommer et al, 2001). For example, one large cohort study found an increased prevalence of 34.1% for mixed-handedness in subjects diagnosed with schizophrenia (best estimate of the prevalence of mixed-handedness in the general population based on meta-analysis: 9.33%, Papadatou-Pastou et al (2020)) that was further associated with increased positive symptoms and a current depressive episode (Mallet et al, 2022).…”
Section: Introductionmentioning
confidence: 87%
“…Moreover, they can investigate possible small study bias in the literature and importantly allow for moderator analyses to investigate variables that could moderate the prevalence of handedness categories among twins (Maxwell, Lau, & Howard, 2015). Indeed, the vast field of handedness has recently seen an upsurge of meta-analyses that aim to summarize the literature and provide estimates of atypical handedness in various populations (e.g., individuals with autism (Markou, Ahtam, & Papadatou-Pastou, 2017), deaf individuals (Papadatou-Pastou & Sáfár, 2016), intellectually disabled and intellectually gifted individuals (Papadatou-Pastou & Tomprou, 2015), individuals with ADHD (Nastou, Ocklenburg, & Papadatou-Pastou, 2020)). Sicotte et al (1999) do report a meta-analysis of the handedness literature in twins.…”
Section: Introductionmentioning
confidence: 99%